Bioinspired polyoxometalates as light-driven water oxidation catalysts - Sánchez-Lara, Eduardo; Favela, Roberto; Castillo, Ivan (Frontiers in Chemical Biology, 2024)
The design of molecular systems with capabilities to carry out the water oxidation reaction and thereby overcome the bottleneck of artificial photosynthesis is one of the scientific fields of most significant interest and urgency due to its potential to address energy demand and climate change. Nevertheless, the search for efficient and robust catalysts has been limited by the degradation of carbon-based ligands under oxidative conditions, leading to the search for fully inorganic catalysts. Polyoxometalates (POMs), an emerging class of carbon-free ligands with oxygen-enriched surfaces, offer a unique alternative as inorganic scaffolds to self-assemble and stabilize transition-metal clusters with unique redox properties. Under catalytic working conditions, POMs can undergo electron transfer reactions coupled to O2 formation without modifying their parental structure. As a result, these materials have recently entered the scene as catalytic players in designing new artificial photosynthetic platforms for water oxidation. We focus on the methods used to create these compounds, their unique structural characteristics, and how effectively they function as catalysts. We also explore the proposed mechanisms behind their ability to produce O2 and their potential use in designing photosynthetic devices.